Child Mentoring to Cultivate Resilience of Vulnerability to Bullying - Susanto Susanto (CV. Creative Tugu Pena, 2023)
Bullying is a severe child problem that needs attention. School-age children are not only vulnerable to becoming victims but also perpetrators. It is a breakthrough intervention so that children are not susceptible to exposure. This community service program aims to cultivate children's resilience to protect themselves from the vulnerability of all kinds of bullying. It employed a mentoring method that involved three stages. The method used Service Learning (SL) method. It was as a medium for integrating voluntary community services with active reflection which is expected to enrich and strengthen training materials in community development with the use of existing assets and potential. They were the preparation, implementation, monitoring, and evaluation stages. The preparatory stage was done by observing school-age children's gathering points, identifying problems, and determining the mentoring program. The second was implementing a mentoring program based on the child's age. Then the third stage was monitoring and evaluation. The mentoring results found that school-age children participated in this program enthusiastically and participative. Knowledge, awareness, and commitment of school-age children in Cilodong, Depok, related to bullying prevention increased significantly. Keywords: Child Mentoring, Cultivate Resilience, Vulnerability to Bullying